Meta-Analysis on Intrinsic Link Between Gender-Based Violence and Socio-Economic Disparity in Domestic and International Ambits - Sana Akhter; Khurram Baig; Jibran Jamshed; Ayesha Khan (Journal of Management Practices, Humanities and Social Sciences, 2021)
Gender-based violence is a deep-rooted problem and stems from the patriarchal structures of societies by virtue of which the laws existent on an international and national level have got little to no implementation. Domestic violence is considered a worldwide epidemic that stems its roots from Gender-based violence; it limits and exploits the rights and freedom of women. The objectives of this paper primarily focus on gender-based violence on a global scale, targeting the loopholes existent in International law. It further creates a linkage between gender-based violence and Human rights, primarily focusing on the hindrance caused by domestic traditions that are existent on a national level. Following the normative legal approach methodology of literature and content analysis. The findings and ramifications of gender-based violence have a lasting impact on the psychology of an individual thus, there’s an imperative need to take steps to curb it on a domestic as well as on an international level. Among the main implications of this research is the introduction of laws on an international level, along with a proper clarification of the ambiguities prevalent in International treaties and laws, which would pave the way for the curtailment of gender-based violence on a broader scale, along with a reduction in the lasting impacts on the psychology of women. The original contribution of this research focuses on putting the responsibility on state governments to protect such a vulnerable group and analyze how their behavior is governed by way of International law. The study also aims at discussing the intrinsic link between gender-based violence and socio-economic disparity. Future research directions and policy implications are suggested.